ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI KOMBINASI ANKLE PUMPING EXCERSICE DAN ELEVASI KAKI 30 DERAJAT UNTUK MENURUNKAN EDEMA TUNGKAI KAKI PADA PENDERITA CKD (CHRONIC KIDNEY DISEASE) SALAH SATU KLINIK HEMODIALISA DI JAKARTA TIMUR - Dinda Nur Aliya (2023)
Chronic kidney failure or also known as Chronic Kidney Disease (CKD) is where the kidneys experience a condition of gradual decline in function. Patients with kidney failure who experience weight gain or Intradialitic Weight Gain (IDWG) because fluid and food intake is not limited as much as 5.7%, causing shortness of breath, edema in the body, swelling in the legs, an increase in uremia, and the occurrence of complications other. This study aims to determine the effectiveness of ankle pumping exercise therapy and 30 degrees elevation in reducing edema in the legs. This intervention is carried out in patients with renal failure who experience leg edema. Ankle pumping and elevation are given 9x/day within 10 minutes for 5 seconds once. The results obtained after carrying out the innovative intervention that ankle pumping and 30 degree elevation of the feet are effective in reducing leg edema is evidenced by the results of the degree of edema in managed patients at the first meeting there was a decrease in the degree of edema from +4 to +3 degrees and at the second meeting there was no edema in the legs, while the patient resumed at the first meeting +4 to +3 and the second meeting +2 to +1. Ankle pumping and 30 degree elevation of the feet can improve and expedite the circulation of blood vessels to reduce leg edema in patients with chronic kidney failure.